Bernard Stiegler’s Conception of Human Being in the Context of Transhumanism and Posthumanism - Sapeńko, Roman; Kłos-Czerwińska, Paulina (Sensus Historiae, 2020)
Both, posthumanism and transhumanism, are an attempt to cross over the limitations of humanism. They focus on the necessity of the transformation of humans as a species, they undermine the traditional understanding of subjectivity and identity. In comparison with transhumanism, which resembles more romantic and futurological humanism, posthumanism seems to be more radical in its assumptions. It is an attempt to stop thinking humans as the undeniably unique and independent, what overthrows the assumptions of traditional humanism. Both areas of research indicate the importance of the limits beyond which the thought about the future of man becomes the apofathic reflexion on post-identity. Bernard Stiegler’s ideas seem interesting in this regard. His thought on human being follows sometimes in the same direction as posthuman thought. At the same time, it underlines the moment of freedom and creation in humans and it opposes new models of life to technological reduction, as it is thought in posthumanism and transhumanism. However, it does not dismiss posthuman thought, but warns against thoughtlessness in crossing over the boundaries of human subjectivity and independence: human being may cross the borders of its subjectivity when it equips the machine with the ability of crossing its boundaries, what implies that it may deposit freedom in machine’s hands.